TODAY’S INTERPRETATION OF OIL AND GAS COMPANIES’ SUSTAINABILITY ON GLOBAL FUEL AND ENERGY MARKET - I. V. Kostenok; Ya. V. Khomenko; A. V. Efimenko (Вестник Российского экономического университета имени Г. В. Плеханова)
The current market is characterized by sharp contradictions between traditional and new centers of power, high competition on fuel and energy market, diversity of natural sources of hydro-carbons and drastic technological changes in oil and gas industry. The article shows a new approach to defining sustainability of oil and gas companies on the global fuel and energy market. Through three principle provisions – ‘sustainability of standing – sustainability of internal situation – structural sustainability’ the authors show today’s features of sustainability of leaders on fuel and energy market. Academic and methodological innovation gives an opportunity to assess objectively the mentioned aspects of sustainability and work out recommendations for market participants. This innovation is based on a set of estimation indicators of leading oil and gas companies, with their help through comparative analysis the generalized criteria of sustainability are calculated and the final indicator – the index of sustainability of Oil and Gas Company – is found. Within the frames of the research such companies as ExxonMobil (US), British Petroleum (UK), PtroChina, SinopecGroup (China), Gasprom, Lukoil and Rosneft (Russian federation) were included. It was shown that raising sustainability of oil and gas companies in the period of global transformations can be promoted by maximum use of the natural and resource potential, increase in the number of deposits, technological renovation of all links in production and sales chain. It is also necessary to design the generalstrategy of response to external challenges and threats on behalf of oil and gas companies belonging to one state (joint sustainability).